2012
DOI: 10.3389/fnbeh.2012.00064
|View full text |Cite
|
Sign up to set email alerts
|

Learning on Jupiter, learning on the Moon: the dark side of the G-force. Effects of gravity changes on neurovascular unit and modulation of learning and memory

Abstract: On earth, gravity vector conditions the development of all living beings by physically imposing an axis along which to build their organism. Thus, during their whole life, they have to fight against this force not only to maintain their architectural organization but also to coordinate the communication between organs and keep their physiology in a balanced steady-state. In space, astronauts show physiological, psychological, and cognitive deregulations, ranging from bone decalcification or decrease of muscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 133 publications
(134 reference statements)
0
11
0
Order By: Relevance
“…Finally, although the impairment in memory processes in people exposed to WBV are not clearly demonstrated, 32,33 several studies in mice have suggested that alterations of spatial navigation and memory could be induced by gravity changes. 34 This is supported by transcriptomic and proteomic analysis of brain in mice models, 22,35,36 and more recently in humans by magnetic resonance imaging. 4,[37][38][39][40] As also proposed in the field of neurodegenerative disorders, an impairment of the BBB is suggested to induce or accelerate the processes of the memory impairments.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, although the impairment in memory processes in people exposed to WBV are not clearly demonstrated, 32,33 several studies in mice have suggested that alterations of spatial navigation and memory could be induced by gravity changes. 34 This is supported by transcriptomic and proteomic analysis of brain in mice models, 22,35,36 and more recently in humans by magnetic resonance imaging. 4,[37][38][39][40] As also proposed in the field of neurodegenerative disorders, an impairment of the BBB is suggested to induce or accelerate the processes of the memory impairments.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that the space environment may have adverse effects on physical abilities, mood and cognitive functioning (57,58). To determine whether a chronic, low dose of cobalt-57 radiation, simulated microgravity or a combination of the two affect behavior in mice, we are currently performing behavioral assessments on these animals.…”
Section: Figmentioning
confidence: 99%
“…This hypothesis is supported by the existence of a hypothalamic-pituitary-adrenal axis activation induced by vestibular lesions (Gliddon et al, 2003a , b ). Gravity changes could also alter cognitive function via modulation of brain vascular reactivity (Porte and Morel, 2011 ). In addition, high levels of hypergravity induce severe impairments in cognitive abilities which may be associated with brain ischemia (Sun et al, 2009 ).…”
Section: Effects Of Altered Gravity On the Development Of Gravity Senmentioning
confidence: 99%